Tradition through Innovation – "Return to the Future". Issue 10 (February 2019) - Uscinowicz, Jerzy
Abstract: Two thousandth years of history of Christianity proved that a main criterion of a value of church architecture was not based on architectural precursors. This architecture was sacred because it was a carrier of a „truth of God" and – like a liturgical mysteries and iconography art – it was a theological comment. It was a codified language of the transposes of religions essences and orders, into the form of architectural expression. This was in an East Christianity and this happens there up to this day. Art is a constant movement between religion and aesthetics. At that moment it ceases to be a work of art, because it is elevated to the level of theological sphere. Its whole value is participation in the life of the 'Other'. If it is a living symbol, it becomes a sacrament. This paper presents selected examples of interaction between architecture, iconography and theology in contemporary sacred art of the last decade in Poland. It also shows the process of evolution of traditional spatial and functional structures and application of new iconography conventions in the Christian temples. It covers problems in art as well as new essential ideological aspects of symbolical and liturgical nature. The effects of design and creation work presented in this paper, serve as a basis to classify these objects as traditional. This assessment of the synthesis of art achieved here – being always the basis for creating the liturgical mystery play within the Christian Church – is left to the reader himself.